Implementation of Project-Based Learning to Improve the Profile of Pancasila Students (P5) at Poboya State Elementary School - Rismawati; Ponirin; Zakiyah Zahara; Mohammad Ega Nugraha (PT. Global World Scientific, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) through the entrepreneurship theme in the Independent Curriculum at Poboya State Elementary School. The research approach employed is qualitative, utilizing a descriptive method, which focuses on the subjective experiences of teachers and students. Data were obtained through interviews, observations, and project documentation, and analyzed systematically with the stages of reduction, presentation, and conclusion. The results of the study indicate that the Independent Curriculum provides a more comfortable, relevant, and participatory learning atmosphere, with teachers acting as learning facilitators. Differentiated and project-based learning through P5 activities is an effective strategy for shaping students' characters by Pancasila values. The entrepreneurship theme in the project encourages students to think creatively, innovatively, independently, and responsibly. The success of this activity is also supported by the school's readiness to adopt technology and utilize the Merdeka Mengajar platform. Overall, the implementation of P5 at Poboya State Elementary School has created a dynamic, inclusive, and adaptive learning environment for the times.